Contact Organization for Caregivers - Martie Gillen; Carolyn S. Wilken (EDIS)
As an older adult or caregiver for an older adult, you may need to contact multiple agencies and offices if you are seeking medical care. It helps to be organized when you contact these agencies, so you know what questions to ask and have somewhere to write down the answers. This worksheet provides a contact form that will help you keep track of your conversations. This revised 3-page fact sheet was written by Martie Gillen and Carolyn S. Wilken, and published by the UF Department of Family, Youth and Community Sciences, August 2012.